1999
DOI: 10.1523/jneurosci.19-14-05910.1999
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Nitric Oxide Synthase Activation and Peroxynitrite Formation in Ischemic Stroke Linked to Neural Damage

Abstract: Nitric oxide (NO) is a new intercellular messenger that occurs naturally in the brain without causing overt toxicity. Yet, NO has been implicated as a mediator of cell death in cell death. One explanation is that ischemia causes overproduction of NO, allowing it to react with superoxide to form the potent oxidant peroxynitrite. To address this question, we used immunohistochemistry for citrulline, a marker for NO synthase activity, and 3-nitrotyrosine, a marker for peroxynitrite formation, in mice subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
194
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(206 citation statements)
references
References 45 publications
9
194
0
3
Order By: Relevance
“…Nuclear staining for AIF has also been reported in the rat brain at 4 hours of reperfusion after 1 hour of MCAO (Ferrer et al, 2003). An increase in the production of reactive oxygen species (ROS) leads to DNA damage and activation of PARP after MCAO (Zhang et al, 1994;Eliasson et al, 1999). In neuronal culture, activation of PARP is linked to a signaling process that translocates AIF from the mitochondria to the nucleus (Yu et al, 2002;Wang et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Nuclear staining for AIF has also been reported in the rat brain at 4 hours of reperfusion after 1 hour of MCAO (Ferrer et al, 2003). An increase in the production of reactive oxygen species (ROS) leads to DNA damage and activation of PARP after MCAO (Zhang et al, 1994;Eliasson et al, 1999). In neuronal culture, activation of PARP is linked to a signaling process that translocates AIF from the mitochondria to the nucleus (Yu et al, 2002;Wang et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…In experimental stroke, both nNOS and PARP activity were found to be increased (Eliasson et al, 1997;Endres et al, 1997;Eliasson et al, 1999;Goyagi et al, 2003), and gene deletion or pharmacologic inhibition of nNOS or PARP-1 reduced infarct volume (Huang et al, 1994;Eliasson et al, 1997;Endres et al, 1997;Goto et al, 2002). In addition, inhibition of PARP decreased AIF translocation, and knockdown of AIF in Harlequin mice reduced infarct volume after 45 minutes of MCAO (Culmsee et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peroxynitrite levels increase during aging and may contribute to some of the nerve cell damage associated with normal aging [27]. In addition, peroxynitrite-mediated toxicity has been implicated in many age-related neurological disorders including ischemic stroke [26], AD, Parkinson's disease (PD), and amyotrophic lateral sclerosis (ALS) (reviewed in [87]). Although peroxynitrite itself is not a free radical, it is a uniquely damaging molecule because it can initiate strong oxidation reactions through decomposition into a hydroxyl radical and nitrogen dioxide [5].…”
Section: Maintenance Of Gshmentioning
confidence: 99%
“…Furthermore, Andrade et al (4) have shown that exposure of muscle fibers to low peroxide concentrations induced an altered cross-bridge kinetics. Because peroxynitrite is a major oxidative agent in ischemia/reperfusion insults such as heart infarct or atrial fibrillation (1,5,6) and produces a reaction likely to be irreversible in vivo, the nitration of protein tyrosines to 3-nitrotyrosine (7)(8)(9), the level of protein nitration has gained acceptance as a fingerprint of in vivo peroxynitrite-mediated oxidative-stress damage (8). Recent studies have shown that myosin is one of the muscle proteins showing higher levels of 3-nitrotyrosine after atrial fibrillation (1,6) and aging (10).…”
mentioning
confidence: 99%